Copper Oxidation Improves Dodecanethiol Blocking Ability in Area‐Selective Atomic Layer Deposition. Issue 19 (31st May 2022) - Liu, Tzu‐Ling; Bent, Stacey F.
Abstract: In recent years, area‐selective atomic layer deposition (AS‐ALD) has attracted increasing interest for its applications in back‐end interconnect processes, and selective deposition of Al2 O3 is of particular interest because Al2 O3 can serve as an etch hard mask. However, Al2 O3 is one of the most difficult ALD systems to block. In this work, a strategy is presented to enhance the blocking ability of dodecanethiol (DDT) self‐assembled monolayers (SAMs) against Al2 O3 ALD. It is shown that by conducting DDT deposition on a slightly oxidized Cu surface, which is mainly composed of Cu2 O, rather than on a freshly acid‐etched Cu surface, which mainly consists of metallic Cu, the quality of the DDT SAM can be improved. It is further shown that the DDT SAMs formed on Cu2 O‐covered Cu substrates are about 3–4 times more effective in blocking Al2 O3 than that on acid‐etched Cu surfaces when ALD is performed under subsaturation condition. However, as the Cu oxidation process continues, CuO is formed and the blocking ability of DDT degrades. Finally, selective Al2 O3 deposition on DDT‐treated Cu/low‐ k patterns using the combined strategy of Cu oxidation and subsaturation conditions achieves selectivity of 0.99 after 4 nm of Al2 O3 ALD. Abstract : A strategy for achieving better blocking by dodecanethiol (DDT) self‐assembled monolayers (SAMs) for area‐selective atomic layer deposition is demonstrated. The packing of DDT SAMs is improved by partially oxidizing Cu to Cu2 O before forming the DDT SAM.